Recent dynamics in the Portuguese housing market as compared with the European union - Matos, Fátima Loureiro de (2012)
The closing years of the 20th century witnessed profound changes in the European housing market, characterised by an increase in owner-occupied housing; instability of house prices (leading to a serious crisis in some regions, in light of a fall in demand); a change in people's attitude to the housing market, involving a rise in the importance of location, the quality of materials and spaces, environmental sustainability, and architectural and urban innovation. The European Union does not have a common housing policy, which it believes is the responsibility of Member-States. However, it is recognised that the problems related to the socio-urban inclusion of low-income individuals do have an impact on Community policies. Because we are in the midst of a transformation, it is difficult to talk today about the dynamics and policies of housing, the functioning of markets, and thereby about the ways in which public administrations are facing the current crisis of real estate overproduction. This article aims at analysing the dynamics of the housing market in Portugal as compared with other European countries, highlighting the characteristics of demand and supply and the main changes recorded in the last few years.